Pathogenic potential of antibodies to the GABA B receptor - Nibber, A; Mann, E; Pettingill, P; Waters, P; Irani, S; Kullmann, D; Vincent, A; Lang, B (Wiley, 2017)
GABAB receptor (GABABR) autoantibodies have been detected in the serum of immunotherapy-responsive patients with autoimmune encephalitis. This study aimed to investigate the effect of immunoglobulin G (IgG) from a patient with GABABR antibodies on primary neuronal cultures and acute slices of entorhinal cortex. Primary hippocampal neuronal cultures were incubated with serum immunoglobulin from patients with GABABR or AMPA receptor (AMPAR) antibodies for up to 72 h to investigate their effect on receptor surface expression. Whole-cell patch-clamp recordings from layer III pyramidal cells of the medial entorhinal cortex were used to examine the effect on neuronal activity. GABABR surface expression was unaltered by incubation with GABABR antibodies. By contrast, after 24 h application of AMPAR antibodies, AMPARs were undetectable. However, acute application of GABABR IgG decreased both the duration of network UP states and the spike rate of pyramidal cells in the entorhinal cortex. GABABR antibodies do not appear to affect GABABRs by internalization but rather reduce excitability on the medial temporal lobe networks. This unusual mechanism of action may be exploited in rational drug development strategies.